2018
DOI: 10.4314/ijbcs.v11i6.18
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions des producteurs et consommateurs sur le riz africain (<i>Oryza glaberrima</i>)

Abstract: RESUME L'introduction en Afrique du riz asiatique a entraîné la disparition progressive du riz africain (Oryza glaberrima) pourtant utilisé en amélioration variétale. Cette étude a pour objectif de recueillir les perceptions des producteurs et consommateurs sur ce riz africain dans la perspective de sa valorisation. Pour ce faire, un sondage a été réalisé suivant une méthode des quotas à Danyi (Togo) au sein de 30 ménages sur la production et la consommation du riz africain. Les résultats ont montré qu'en dépi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This could be explained by the antiquity of African rice production in this region, which pre-dates the colonial era (Vido 2012), the local eating habits of the populations of the north, and by the importance of African rice in their sociocultural life. Indeed, as rice producers in Burkina-Faso (Kam et al 2003) and as revealed by Gnacadja et al (2017), farmers in northern Benin prefer the taste of local rice varieties, considered as having a good taste. In addition, according to Barry et al (2008), the high proportion of local varieties in a region reflects the predominance of subsistence production systems with low intensification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the antiquity of African rice production in this region, which pre-dates the colonial era (Vido 2012), the local eating habits of the populations of the north, and by the importance of African rice in their sociocultural life. Indeed, as rice producers in Burkina-Faso (Kam et al 2003) and as revealed by Gnacadja et al (2017), farmers in northern Benin prefer the taste of local rice varieties, considered as having a good taste. In addition, according to Barry et al (2008), the high proportion of local varieties in a region reflects the predominance of subsistence production systems with low intensification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that the Republic of Benin has relatively low quality rice which induces a low competitiveness compared to imported rice (Codjo et al 2016), and the success of improved varieties have so far failed to meet the expectations of both producers and consumers (Gnacadja et al 2017). It is, therefore, important that breeders develop new rice varieties adapted to local conditions and that meet the preferences of both producers and consumers in order to boost rice production in the various regions of Benin.…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa, rice represent the second most consumed cereal after maize, while its production does not cover consumption needs [1]. Particularly in West Africa, 60% of the population's needs are covered by local production estimated at 23 million tons in 2018 [2,3]. This production shortfall is under the triple influence of population growth, increased per capita consumption of rice and strong urbanization at the expense of arable land.…”
Section: Ntroductionmentioning
confidence: 99%
“…Indeed, the commercial quality is mainly determined by the physical properties and the name of the variety. The machining degree, the color and the age of milled rice are also indicators of grain quality (Gnacadja et al, 2017). The cooking and consumption quality is determined by the physicochemical properties, in particular, the apparent amylose content (a constituent of starch which represents major part of the milled rice), the viscosity and some other properties (Demont et al, 2013;Ibrahima et al, 2019).…”
Section: Introductionmentioning
confidence: 99%